Android Based Module Development with Project- Based Learning Model on Immune System Materials to Improve Critical Thinking and Digital Literature Skills - Syarofatin, Ririn Hamidatus; Isnaeni, Wiwi; Alimah, Siti (Journal of Innovative Science Education, 2022)
Critical thinking skills and digital literacy are indispensable in 21st-century life. These two skills can be trained through a learning process that uses an Android-based module with a Project Based Learning model. This study aims to analyse the feasibility and effectiveness of android-based modules to improve critical thinking skills and digital literacy. This research is a research development or Research and Development (R&D). The development in this study uses the ADDIE model which consists of five stages, namely Analysis, Design, Develop, Implementation, and Evaluation. The data in this study are module validity, critical thinking skills, and digital literacy. The instrument used in this study consisted of a module validation sheet to measure the feasibility of the module, reasonable multiple-choice test questions to measure critical thinking skills, and an observation sheet to measure digital literacy. The results showed that: 1) the module was declared very valid with an average value of 86.35; 2) the module is declared effective in improving critical thinking skills which are indicated by the N-Gain value of 0.47 with moderate criteria; and 3) the module is declared effective in increasing digital literacy as indicated by the N-Gain value of 0.56 with moderate criteria.